Vertebrate-faunal diversity profile of Sisauli Wetland, Belbari, Morang - Adhikari, Ramchandra; Thapa Chhetry, Damodar (Nepalese Journal of Biosciences, 2017)
The research work on Sisauli Wetland area of Belbari Municipality, Morang was conducted from first week of April to last week of August, 2018. A total of 12 species of mammals, 19 species of Aves, 13 species of reptiles, 8 species of amphibian and 19 species of Pisces were documented from Sisauli Wetland area.